Antioxidant and cytotoxic activity of ethyl asetat extracts of cocoa pod husk (Theobroma cacao L). (November 2019) - Umri, R J; Maulana, I; Ginting, B
Abstract: Isolation of ethyl acetate extract from cocoa pod husks ( Theobroma cacao L ) and testing of their cytotoxic as well as antioxidant activities has been done. The cytotoxic activities test has been carried out employing Brine Shrimp Lethality Test (BSLT) method, while the antioxidant activities test was employing l, l-diphenyl-2-picrylhydrazyl (DPPH) and vitamin C as positive control. In the cytotoxic test, all fractions showed excellent cytotoxic activity with a range of LC50 = ∞ ppm to 107.15 ppm. The extract also showed antioxidant activity with IC50 = 163.35 ppm and vitamin C = 0.014 ppm. Isolation of the active components of ethyl acetate extract using silica gel as stationary phase and n-hexane:ethyl acetate (9:1) eluent, yielded a combination of 9 fractions (TCE1-TCE9). The separation of TCE 5 produced white needle crystals with a melting point of 128 - 131°C. Based on the stain pattern, the crystal belongs to a phenolic compound.